Experimental study of the 15O(2p, γ)17Ne cross section by Coulomb Dissociation for the rp process. Issue 1 (January 2016) - Marganiec, J; Warners, F; Aksouh, F; Aksyutina, Y; Pol, H Alvarez; Aumann, T; Beceiro, S; Bertulani, C; Boretzky, K; Borge, M J; Chartier, M; Chatillon, A; et al.
Abstract: The time-reversed reaction 15 O(2 p, γ) 17 Ne has been studied by the Coulomb dissociation technique. Secondary 17 Ne ion beams at 500 AMeV have been produced by fragmentation reactions of 20 Ne in a beryllium production target and dissociated on a secondary Pb target. The incoming beam and the reaction products have been identified with the kinematically complete LAND-R 3 B experimental setup at GSI. The excitation energy prior to decay has been reconstructed by using the invariant-mass method. The preliminary differential and integral Coulomb Dissociation cross sections (σ Coul ) have been calculated, which provide a photoabsorption (σ photo ) and a radiative capture cross section (σ cap ). Additionally, important information about the nuclear structure of the 17 Ne nucleus will be obtained. The analysis is in progress.